Control of the Length and Density of Carbon Nanotubes Grown on Carbon Fiber for Composites Reinforcement. Issue 1752 (2015) - Cardoso, Lays D. R.; Trava-Airoldi, Vladimir J.; Silva, Fabio S.; Zanin, Hudson G.; Antunes, Erica F.; Corat, Evaldo J.
ABSTRACT: Aligned multi-walled carbon nanotubes were grown on carbon fiber surface in order to provide a way to tailor the thermal, electrical and mechanical properties of the fiber-resin interface of a polymer composite. As the deposition temperature of the nanotubes is very high, an elevated exposure time can lead to degradation of the carbon fiber. To overcome this obstacle we have developed a deposition technique where the fiber is exposed to an atmosphere of growth for just one minute, and different concentrations of precursor solution were used.